Characterisation of microstructure and mechanical properties in Al–Mg alloy with addition of Sc and Zr. (July 2014) - Jiang, F.; Zhou, J.; Huang, H.; Qu, J.
<x content-type="archive" xml:space="preserve">Abstract</x> The characterisation of microstructure and properties of Al–Mg–Sc–Zr alloy was reviewed. The strengthening mechanism, corrosion resistance, weldability, fatigue and fracture toughness of the Al–Mg–Sc–Zr alloy were summarised and analysed according to the research studies in recent years. Compared with traditional Al–Mg series alloys, combined addition of Sc and Zr increases the strength of Al–Mg based alloys remarkably while keeping excellent comprehensive properties (such as corrosion resistance). The trace elements (Sc and Zr) could precipitate the dispersive distribution of Al3(Sc, Zr) phase, which could refine the casting structure of the Al–Mg alloy and increases the strength notably. The Al3(Sc, Zr) precipitation, which keeps an LI2 structure and retains a coherent lattice relationship with Al matrix, has a significant effect on pinning dislocation and hindering motions of grain boundary. As a result, the recrystallisation temperature of Al–Mg–Sc–Zr alloy is elevated apparently. There is also significant effect on the corrosion resistance, weldability, fatigue and fracture toughness of Al–Mg–Sc–Zr alloy.